THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, INDEPENDENCE LEARNING, AND PARENT’S ATTENTION WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS MTs MUHAMMADIYAH KARANGKAJEN - Hasanatul Fu'adah Amran; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2017)
The result of low mathematics learning related to several factors. The relationship between numerical skills, independent learning, and parent’s attention are the factors that may be linked to learning outcomes. The research is intended to know about is there any positive correlation and significance or not between numerical ability, independence learning, and parent’s attention with mathematics learning outcomes in students class VII in odd semester of MTs Muhammadiyah Karangkajen Yogyakartar in the academic year of 2016/2017. The population in this research was the students of VII grade in MTs Muhammadiyah Karangkajen Yogyakartar in the academic year of 2016/2017, consisted of class VIIA, VIIB, VIIC, VIID, and VIII, totaling 150 students. Samples were taken from VIIE as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of independent learning and parent’s attention, and test method to get the numerical ability and result learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between numerical ability, independence learning, and parent’s attention with mathematics learning outcomes in students class VII in e odd semester of MTs Muhammadiyah Karangkajen Yogyakartar in the academic year of 2016/2017. It is showed by Fcount Ftable is 7,4503 > 2,9912 with R = 0,6870 and R2 = 0,4720 with , with SR = , SR = and SR = 35,5476 , SE = , SE = and SE = .